DYNAMICS OF FAMILY LAW REFORM IN THE MUSLIM WORLD (STUDY ON THE AGE LIMITS FOR MARRIAGE IN INDONESIA, MALAYSIA, BRUNEI DARUSSALAM) - Septiani, Rina (JURNAL ILMU SYARIAH, 2023)
Family law occupies a very important position in Islamic law, related to its very significant contribution in the effort to create an orderly and harmonious society. That is why in many Islamic countries or where the majority of their citizens are Muslim, especially Indonesia, Malaysia, Brunei Darussalam, the field of family law always gets high appreciation which is manifested in the form of ongoing efforts to legislate Islamic law into positive law into statutory products. Renewal of Islamic family law in Indonesia, Malaysia, Brunei Darussalam is a necessity. In terms of the age limit for marriage, there are differences in the three countries. years, contained in Deed 303 of the 1984 Islamic family law section 8, Brunei Law Chapter 217 Chapter 17 Islamic Family law section IV article 35 letter (6) says 18 years for men and 16 years for women so for those who prevent marriage above age will be penalized. Even though they both belong to the Syafii school of thought, their views on fiqh, culture, and society are different, so there are differences in the determination of age limits between the three countries.